2012
DOI: 10.1103/physrevlett.108.167402
|View full text |Cite
|
Sign up to set email alerts
|

Phonon-Assisted Optical Absorption in Silicon from First Principles

Abstract: The phonon-assisted interband optical absorption spectrum of silicon is calculated at the quasiparticle level entirely from first principles. We make use of the Wannier interpolation formalism to determine the quasiparticle energies, as well as the optical transition and electron-phonon coupling matrix elements, on fine grids in the Brillouin zone. The calculated spectrum near the onset of indirect absorption is in very good agreement with experimental measurements for a range of temperatures. Moreover, our me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
179
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 37 publications
4
179
1
Order By: Relevance
“…While the direct transition probabilities were elucidated in the 1960s, [14][15][16][17] transitions of type (1), due to the vast need for computer power, were calculated by first principles only quite recently. 18 Transitions (1) and (2) are reflected in experimental data for the absorption coefficient, a, measured at room temperature by Aspnes and Studna 19 and shown in Fig. 2(b).…”
Section: Light Absorption In Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…While the direct transition probabilities were elucidated in the 1960s, [14][15][16][17] transitions of type (1), due to the vast need for computer power, were calculated by first principles only quite recently. 18 Transitions (1) and (2) are reflected in experimental data for the absorption coefficient, a, measured at room temperature by Aspnes and Studna 19 and shown in Fig. 2(b).…”
Section: Light Absorption In Siliconmentioning
confidence: 99%
“…The total number of absorption events expressed by the coefficient a(h ), only produces a fraction of electrons at final states which gives rise to carrier emission. A rigorous solution of this problem, to find an absorption coefficient for transitions leading to emission, would require a first principle calculation similar to the one by Noffsinger et al 18 but for transitions with final states above E b only.…”
Section: Emission Across the Oxide Barriermentioning
confidence: 99%
“…Silicon and SiC both have an indirect band gap meaning that the VBM and CBM are separated in k-space. Recently there was a theoretical study about the phonon-assisted optical absorption in silicon, which showed the difficulties in calculations of indirect band gap materials [9]. The indirect band gap is 1.12 eV for silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect transitions can also lead to significant absorption, however-as is evident from the use of indirect-band-gap materials such as silicon in photovoltaics. 5 The large concentration of electrons in the conduction band, combined with the potentially large density of states available throughout the Brillouin zone that are made accessible in indirect processes, can lead to sizable absorption that sets a fundamental limit on the transparency of the TCO. has a band gap of 3.6 eV.…”
Section: Introductionmentioning
confidence: 99%